Aktivitas Antibakteri Sediaan Masker Gel Peel Off Ekstrak Mentimun (Cucumis Sativus) Dan Tomat (Solanum Lycopersicum) Terhadap Staphylococcus Epidermidis - Indri Dwi Rahasasti; Eva Luviriani; Rosellynia Calyptranti; Triani Kurniawati; Lia Handayani Rahayu (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2024)
Acne is a disease that can be caused by bacteria, one of which is Staphylococcus epidermidis. Acne can be treated with active compounds derived from natural ingredients such as cucumbers and tomatoes. Gel masks peel off. This study aims to determine the average diameter of the inhibition zone, the difference in the average diameter of the inhibition zone, and the antibacterial activity of the peel-off from a mixture of cucumber (Cucumis sativus) and tomato (Solanum lycopersicum) with a concentration of 5%, 10 %, 15%, 20% against Staphylococcus epidermidis. This experimental study uses a Completely Randomized Design (CRD) consisting of one factor and 6 levels. The results showed that the average diameter of the inhibition zone of the anti-acne peel-off gel mask preparation of cucumber and tomato extracts against Staphylococcus epidermidis at a concentration of 5%, 10%, 15% and 20% were 16.38 mm, respectively. ; 24.88 mm; 29.88 mm and 34.88 mm. There was a significant difference in the average diameter of the inhibition zone of the peel off mixture of cucumber and tomato extracts with a concentration of 5%, 10%, 15%, and 20%; against Staphylococcus epidermidis. gel mask preparation peels off from a mixture of cucumber and tomato extracts against Staphylococcus epidermidis at a concentration of 5%, 10% concentration, 15% concentration and 20% concentration, namely strong, very strong, very strong and very strong.